The Role of Ceramide Synthases in the Pathogenicity of Cryptococcus neoformans - Mansa A. Munshi; Justin M. Gardin; Ashutosh Singh; Chiara Luberto; Robert Rieger; Tejas Bouklas; Bettina C. Fries; Maurizio Del Poeta (Cell Reports, 2018)
Summary: Cryptococcus neoformans (C. neoformans) is estimated to cause about 220,000 new cases every year in patients with AIDS, despite advances in antifungal treatments. C. neoformans possesses a remarkable ability to disseminate through an immunocompromised host, making treatment difficult. Here, we examine the mechanism of survival of C. neoformans under varying host conditions and find a role for ceramide synthase in C. neoformans virulence. This study also provides a detailed lipidomics resource for the fungal lipid research community in addition to discovering a potential target for antifungal therapy.